Gastroesophageal reflux disease and irritable bowel syndrome - prevalence and overlap. - Patrycja Kmiotek; Andrzej Materniak (Kazimierz Wielki University, 2019)
Introduction Irritable bowel syndrome (IBS) belongs to the group referred as functional gastrointestinal disorders. IBS is manifested by abdominal pain or discomfort in association with frequent diarrhea or constipation and a change in bowel habits, which are not caused by organic or biochemical changes. Because of the lack of specific markers or tests, diagnosis is based on the symptoms. In recent years there have been many reports about patients with IBS also presenting gastroesophageal reflux symptoms more commonly than healthy population. Aim of the study The aim of our study was to determine the prevalence and possible theories about irritable bowel syndrome and gastroesophageal reflux disease (GERD) overlap. State of knowledge Analyzed studies proves significant overlap of IBS and GERD. Theories explaining the co-existence of IBS and GERD says that both disorders are presented in significant number of patients, which is related with smooth muscle motor disorder in gastrointestinal tract. Other theories suggests that IBS-like symptoms are part of the spectrum of GERD manifestation, due to relief of IBS-like symptoms in GERD patients who are receiving anti-reflux treatment. Our study collect main reports about co-existence and common causes of GERD and IBS. Conclusions Studies highlights the importance of identifying overlapping functional gastrointestinal conditions as a therapeutic strategy for better management of GERD. Because of the strong association of IBS with GERD, it has been recommended that physicians who recognize, and treat IBS patients should also screen them for the co-existence of GERD.